The relationships between self-esteem, emotional reactions and quality of life in pediatric locomotory trauma patients - Jonovska, Suzana (Array, 2009)
Abstract: The main aim of this study was to establish the relationships between several psychosocial characteristics in children and adolescents differently treated for isolated long tubular bones’ fractures. Examined variables were: self-esteem, basic emotional reactions toward illness or injury including depression and anxiety, as well as perception of quality of life and social support during the treatment. Whole sample comprehends 135 patients, both gender, 10–18 years of age, treated for mentioned fractures in period 2003–2005 at the Departments of Pediatric Surgery of 3 hospitals: University Hospital Centre in Rijeka and Clinical Children’s Hospital in Zagreb, both in Croatia and University Hospital in Mostar, BiH. 73 patients were treated conservatively (CT), 40 of them underwent Elastic Stable Intramedullary Nailing (ESIN) and 22 of them underwent other surgical techniques (OST).